Electrochemical properties of modified conductive PANI coatings - Poh, Bi Juan. (2009)
For the past years, conductive polymers have been widely researched for their applications such as rechargeable batteries, electro-catalysts and electrical appliances due to their excellent conductivity properties. There are many methods that have been approached, such as electro-chemical, chemical, photo-chemical, enzyme-catalyzed and dip coating. In the previous project, fabrication of conductive polymeric coatings is produced by means of dip coating. Carbon black nano particles are used as conductive dopant to Polymethyl-methacrylate (PMMA) with toluene to form polymer coatings. In this report, another method – electro-chemical deposition, is approached. Aniline solution is added to sulphuric acid, and cyclic voltammetry method is applied to form conductive Polyaniline (PANI) coatings on P-silicon substrate. Followed on, silver nitrate as an additive is added into the solution to fabricate modified PANI coatings. Two different methods are approached to fabricate PANI coatings. First method is to dope silver particles into PANI matrix, while the second method is to deposit silver particles onto the PANI coatings. The number of scan cycles is varied to study their electro-chemical properties – charge transfer resistivity. In the experiment, Electro-chemical Impedance Spectroscopy (EIS) is used to study the coatings’ charge transfer resistivity. On the whole, it was determined that PANI coatings fabricated using cyclic voltammetry have excellent charge transfer resistivity, but the adding of silver particles had negative impacts.